Barok na Slovenskem : sakralni prostori - Kemperl, Metoda; Vidmar, Luka; Smerke, Marjan (Ljubljana : Cankarjeva založba, 2014)
Summary -
Bibliografija: str. 260-268 -
Keywords: slovenski barok, arhitektura -- arhitektura baroka